Thorstein Veblen and the enrichment of evolutionary naturalism - Tilman, Rick (University of Missouri Press, 2007)
"Tilman argues that evolutionary naturalism provides the philosophical foundations of Veblen's thought. He links evolutionary naturalism to Veblen's aesthetics, secular humanism, sociology of control, sociobiology, and sociology of knowledge, thereby initiating observations regarding the relationship of Veblen's own life to his thinking and his place as a cultural lag theorist"--Provided by publisher.